Thermal shock-stabilized metal catalysts on oxide hemitubes: Toward ultrasensitive chemiresistors - Chae, Soohwan; Ahn, Jaewan; Nam, Jong Seok; Jang, Ji-Soo; Kim, Il-Doo (Elsevier BV, 2022)
To achieve powerful gas sensors oxide semiconductor chemiresistors, the uniform functionalization of nano catalysts on the desired metal oxides is considered as a key strategy. However, still, it is challenging to achieve the nanocatalysts decoration on desired oxides without deterioration of target materials. In this study, thermal shock (rapid joule-heating method) was applied to uniformly decorate Pt nanoparticles (NPs) on the surface of carbon nanofibers (CNFs) to achieve the uniform distribution of Pt NPs on one-dimensional structures. And then, SnO2 was physically deposited on the Pt NPs loaded CNFs and continuous heat-treatment was conducted to transfer the Pt NPs to desired SnO2 porous hemitubes. Thanks to the well-distributed Pt NPs on porous SnO2 hollow structures, the Pt laoded SnO2 hemitubes showed an exceptional sensitivity (R-air/R-gas = 1500 at 5 ppm) in H2S. Also, it showed high selectivity for H2S and high stability even under continuous gas exposure, confirming its potential as an effective H2S sensor.